The Effectiveness of The Color Lamp on The Diversity of Insects in Onion Plantations - M Abdu Na'im; Mohamad Nasirudin (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Onions (Allium cepa L) are horticultural commodity that cannot be abandoned by people in everyday life. One of the limiting productivity of onions is pest and disease attack. Study of insect diversity is the first step in controlling pests in plants. The common alternative used by farmers to eradicate insect pests that do not damage the environment is using lights at night as a trap media. This study identified the diversity of insects that correlate to onions which are attracted to the color of the light that have been installed using 5 light colors, namely red, blue, white, yellow, and green. Insect diversity index found in this study contained 16 families, as many as 14,048 entity. Consisting of Chrysomelidae, Coccinellidae, Nitidulidae, Anthicidae, Delphacidae, Alydidae, Cucujidae, Noctuidae, Tipulidae, Agromyzidae, Cecidomyiidae, Tettigoniidae, Acrididade, Thripidae, Ichneumonidae, and Cicadellidae. The value of the diversity index(H') of insects in red is 1.78, yellow is 2.19, green is 2.28, white is 2.12 and blue is 0.74. The diversity on red, yellow, green, and white color is moderate, while blue color show low diversity. The dominance index in red is 0.28, yellow is 0.17, green is 0.14, white is 0.20, and blue is 0.66. This shows that the land has variety of insect species and there is no insect species that dominate.